Review of The Avant-Garde Flute: A Handbook for Composers and Flutists by Thomas Howell and The Other Flute: A Performance Manual of Contemporary Techniques by Robert Dick - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1976)